Subcellular Structures and Function of Myocytes Impaired during Heart Failure are Restored by Cardiac Resynchronization Therapy - Sachse, Frank B. (2012)
RATIONALE: Cardiac resynchronization therapy (CRT) is an established treatment for patients with chronic heart failure. However, CRT associated structural and functional remodeling at cellular and subcellular level is only partly understood. OBJECTIVE: To investigate the effects of CRT on subcellular structures and protein distributions associated with excitation-contraction coupling of ventricular cardiomyocytes. METHODS AND RESULTS: Our studies revealed remodeling of the transverse tubular system (t-system) and the spatial association of ryanodine receptor (RyR) clusters in a canine model of dyssynchronous heart failure (DHF). We did not find this remodeling in a synchronous heart failure model based on atrial tachypacing. Remodeling in DHF ranged from minor alterations in anterior left ventricular myocytes to nearly complete loss of the t-system and dissociation of RyRs from sarcolemmal structures in lateral cells. After CRT, we found a remarkable and almost complete reverse remodeling of these structures despite persistent left ventricular dysfunction. Studies of whole cell Ca(2+) transients showed that the structural remodeling and restoration were accompanied with remodeling and restoration of Ca(2+) signaling. CONCLUSIONS: DHF is associated with regional remodeling of the t-system. Myocytes undergo substantial structural and functional restoration after only 3 weeks of CRT. The finding suggests that t-system status can provide an early marker of the success of this therapy. The results could also guide us to an understanding of the loss and remodeling of proteins associated with the t-system. The steep relationship between free Ca(2+) and contraction suggests that some restoration of Ca(2+) release units will have a disproportionately large effect on contractility.